Assessment of Frequency and Contributing Risk Factors Associated with the Development of Mammary Fistula After Incision and Drainage in Cases of Breast Abscess: A Single-Center Experience - Ahmad, Zarka; Ullah, Zia; Sarwar, Saeed; Ullah, Izaz; Khan, Muhammad Amin; Rahman, Obaid ur; Zarin, Mohammad (Biological and Clinical Sciences Research Journal, 2025)
A breast abscess is a localised collection of pus within the breast parenchyma, typically developing under the skin. In most cases, it occurs as a result of a bacterial infection. Management includes oral and IV antibiotics, percutaneous needle aspiration, ultrasound-guided aspiration, and incision and drainage. U/S guided aspiration is currently the standard treatment. A mammary fistula is a complication of breast surgery or other therapeutic interventions. A Mammary Fistula is defined as an abnormal communication between the lactiferous duct and breast skin. Treatment options include fistulectomy, primary closure and total duct excision. Postoperative wound infection is a primary factor in fistula recurrence. Objective: This study aims to determine the frequency of mammary fistula following incision and drainage in patients with breast abscesses. And also characterise the associated risk factors. Methods: A retrospective chart analysis was conducted at Khyber Medical Centre, Peshawar, Pakistan, from March 2023 to November 2023. Patients presenting with breast abscesses, irrespective of type, confirmed on clinical examination and radiologic findings, were included in the study. Abscesses in patients with breast cancer or suspicious of malignancy, and post-oncological surgical procedures, were a part of the exclusion criteria. Data was collected from patients’ records using a self-administered data collection tool. The data were analysed using SPSS version 26.Results: The Mean age of the population was 27.8 years, with an average range between 20 and 37 years. Among the types of breast abscesses, lactational abscesses were the most common, affecting 35 (85.4%) patients. The peri-areolar incision group had a milk fistula in 7 out of 9 patients. Only two cases were reported with radial incisions. All patients with fistula had a stab incision and drainage (100%), while no case was reported in patients with incision drainage with penrose drain insertion. Conclusion: Mammary Fistula is not a common complication of therapeutic incision and drainage. It primarily affects young lactating women and is a sequel to breast abscess. The location of the abscess and the incision site are contributing factors. Peripherally placed incisions are safer than central incisions.